2019
DOI: 10.17977/um022v4i12019p049
|View full text |Cite
|
Sign up to set email alerts
|

Studi kesesuaian dan strategi pengelolaan ekowisata Pantai Ungapan, Kabupaten Malang untuk pengembangan pariwisata berkelanjutan

Abstract: One form of utilization of coastal and marine resources in Malang Regency is the development of coastal tourism areas. In this case the form of coastal tourism developed is coastal recreation activities. The purpose of this study was to analyze the suitability of recreational tourism and formulate a strategy for managing coastal tourism areas. This research was conducted at Ungapan Beach in Gajahrejo Village, Gedangan District, Malang Regency, East Java. The method used in this study is descriptive with quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 3 publications
0
10
0
8
Order By: Relevance
“…According to Insani (2019) results means determining the measurement of the results to be achieved (measurable results) as strategic planning, to determine the extent to which the goals have been mutually agreed upon. The Pakuhaji Village Government has a function or positions itself as a facilitator to achieve successful development through community empowerment in the following ways:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Insani (2019) results means determining the measurement of the results to be achieved (measurable results) as strategic planning, to determine the extent to which the goals have been mutually agreed upon. The Pakuhaji Village Government has a function or positions itself as a facilitator to achieve successful development through community empowerment in the following ways:…”
Section: Resultsmentioning
confidence: 99%
“…According to Insani et al (2019) opportunities are things that are analyzed against the external environment to identify the best opportunities one has. The external environment is an area filled with all kinds of possibilities and opportunities.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Dreamland beach had a base material of white sand which was very suitable. Compared to Ungapan Beach in Malang with the base material of mud [6] then, it can be concluded that Dreamland was more suitable considering beaches with mud as its base material are not suitable as a tourist destination [22]. According to Yulianda [19] base material of the water was one of the most prominent parameters to determine the suitability of a beach as a tourism site considering one activity often done on a beach was to play with sand.…”
Section: Tourism Suitability Indexmentioning
confidence: 99%
“…Sehingga memperhatikan kesesuaian lahan dengan memanfaatkannya sebagai objek pariwisata penting dengan memahami dan menjaga agar karateristik lingkungan tetap sesuai dan berkelanjutan. (Insani et al, 2019).…”
Section: Lingkunganunclassified